Isolation of two steroidal saponins with antileishmanial activity from Allium giganteum L. - Farnaz Chaparian; Zeinab Delazar; Masoud Sadeghi Dinani (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: Alliums are rich sources of steroidal saponins, flavonoids, and sulphoric compounds of which steroidal saponins have recently received more attention due to their important pharmacological activities. Allium giganteum (giant onion) which is named locally "Couria" in the Northeast of Iran, is grown widely in "Kouh-Sorkh" mountains in Khorasan province. Experimental approach: Phytochemical investigation of chloroform-methanol and aqueous extract of the plant resulted in the isolation and identification of two steroidal saponins, using comprehensive spectroscopic methods including 1D and 2D NMR and MS. Findings/Results: The chemical structures of the isolated saponins were determined as (22S)-cholesta-1b,3b,16b,22b-tetraol 5-en, and 3-O-β-D-glucopyranosyl26-O-β-D-glucopyranosside and (25R)-26-O-β-D-glucopyranosyl-5α-furostan-1α,3β,22α,26-tetraol3-O-{β-D-galactopyranosyl-(1→2)-O-[β-D-xylopyranosyl- (1→3)]-O-β-D-glucopyranosyl-(1→4)-β-D-galactopyranoside}. Investigation of in vitro antileishmanial activity of the isolated compounds at 10, 50, and 100 μg/mL exhibited significant leishmanicidal against the promastigotes of Leishmania major. Conclusion and implications: The results established a valuable basis for further studies about A. giganteum and the anti-parasitic activity of steroidal saponins.